TEXNOLOGIK TA’LIM YO‘NALISHIDA UMUMKASBIY VA IXTISOSLIK FANLARI INTEGRATSIYASINI TA’MINLASh - Orınbetov, N.T. (SCIENCE and SOCIETY, 2024)
The article discusses the organization of professional activities of future technology teachers based on the integration and interconnection of general professional and specialized disciplines of the bachelor’s degree program in the higher education system. It also presents proposals for identified problems and relevant methodological recommendations.
Keywords: professional activity; integration; innovation; modernization; knowledge; skills; general professional and specialized disciplines; higher education; bachelor; continuity; specialty; education system